Best Nursing Intervention Practices to Prevent Non-Communicable Disease: A Systematic Review - Mercedes Gomez del Pulgar; Mercedes Gomez del Pulgar; Miguel Angel Cuevas-Budhart; Sonsoles Hernández-Iglesias; Maria Kappes; Veronica Andrea Riquelme Contreras; Esther Rodriguez-Lopez; Alina Maria De Almeida Souza; Maximo A. Gonzalez Jurado; Almudena Crespo Cañizares (Frontiers Media S.A., 2022)
Objectives: To explore nursing health education interventions for non-communicable disease patients.Methods: The design was a systematic review of research work published between 2008 and 2018. The data sources included the Web of Science, PubMed, Scopus, COCHRANE, and LILACS. The studies that met the inclusion were assessed, and the analysis for methodological quality through the recommended tools CASPe, and JADAD.Results: Fifteen original studies from eight counties were included in the review; Findings revealed 13 studies with randomized samples and six used power analysis. Nurses' interventions included house calls, home care, and individual and group health education.Conclusion: Nursing interventions showed 76.4% the effectiveness of results in patient outcomes to promote and improve healthier lifestyles and quality of life of non-communicable disease patients. This review discloses the significant impact of nursing health education interventions. Nursing leadership and political decision-makers should consider providing programs to enhance health education knowledge and abilities. All of this can favor the sustainability of the global economy by changing the life style of thousands of people worldwide.Systematic Review Registration:https://www.crd.york.ac.uk/prospero/, identifier CRD42020208809.